2002
DOI: 10.1093/ajcn/76.4.845
|View full text |Cite
|
Sign up to set email alerts
|

Negative calcium balance during lactation in rural Mexican women

Abstract: Negative calcium balance was observed during lactation in rural Mexican women who consumed a high-fiber diet. Furthermore, the data suggest that the hormones estradiol and PTHrP are involved in the regulation of calcium balance and of the calcium content of milk during lactation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 34 publications
1
12
0
1
Order By: Relevance
“…A large percentage of women consumed whole milk and yogurt in their diets, which are adequate sources of calcium; however, calcium intakes must be taken with caution, because bone metabolism during and after lactation is poorly understood. In a study with rural Mexican women [25], calcium balance was negative at 1, 3 and 6 months post-partum. Taking into account calcium availability, it is of concern that some of the women in our study had low calcium intakes.…”
Section: Food Components Of Mexican Lactating Womenmentioning
confidence: 93%
“…A large percentage of women consumed whole milk and yogurt in their diets, which are adequate sources of calcium; however, calcium intakes must be taken with caution, because bone metabolism during and after lactation is poorly understood. In a study with rural Mexican women [25], calcium balance was negative at 1, 3 and 6 months post-partum. Taking into account calcium availability, it is of concern that some of the women in our study had low calcium intakes.…”
Section: Food Components Of Mexican Lactating Womenmentioning
confidence: 93%
“…The PTHrP concentration of milk (245,812,941) and in the maternal circulation (245) correlates positively with total milk calcium content. A randomized trial found no effect of calcium supplementation on milk PTHrP content, but there may be a diurnal variation with more PTHrP in milk obtained in the morning compared with the afternoon (208).…”
Section: Human Datamentioning
confidence: 96%
“…Although a study of rural Mexican women found that women who were lactating had higher 1,25(OH) 2 D than age-matched non-lactating women [147], many studies show that the elevated levels of 1,25(OH) 2 D 3 seen in pregnancy decrease back to normal levels [148,149]. However, in support of the role of prolactin in vitamin D metabolism during lactation, a patient with hypoparathyroidism was found to require less exogenous vitamin D supplementation during lactation than at other times [150].…”
Section: Prolactinmentioning
confidence: 94%
“…Clinically, plasma 1,25(OH) 2 D 3 levels are elevated in human pregnancy and remain high postpartum in lactating women [147,148] (see Chapter 38). Levels of 25(OH)D in pregnant women are similar to those of controls [208].…”
Section: Estradiolmentioning
confidence: 99%